Deep brain stimulation in psychiatry - Mohr, Pavel (Neuro endocrinology letters, 2008)
Deep brain stimulation (DBS) is a reversible surgical procedure that involves stereotactic implantation of electrodes into the targeted brain regions, with a subcutaneously placed pulse generator powering the electrodes via one or two leads. The mechanism of action can be explained by the stimulation-induced modulation of impaired network activity. So far, the main use of DBS has been for neurological conditions, such as essential tremor, motor symptoms in Parkinson's disease, dystonia, epilepsy, and chronic pain. In psychiatry, case series and open studies indicate treatment efficacy of DBS in Gilles de la Tourette syndrome, treatment-resistant obsessive-compulsive disorder, and refractory major depression. Neuroimaging studies have confirmed the effects of DBS on the brain regions implicated in specific neuropsychiatric disorders. It is a well-tolerated method with relatively few serious side effects. Additional well-designed and appropriately powered controlled clinical trials are needed to conclusively establish the efficacy and safety of DBS and to identify the patient population(s) who may benefit most. Ongoing research with stimulation techniques may also significantly contribute to our understanding of major neuropsychiatric disorders.
Keywords: Deep Brain Stimulation; Mental Disorders; lidé; psychiatrie; Psychiatry; Treatment Outcome; hluboká mozková stimulace; výsledek terapie; duševní poruchy; Humans